Perbandingan Kebijakan Formulasi Ganja di Kanada dan Uruguay Dikaitkan dengan Hukum Pidana Indonesia - Shinta Chintya Fella; Syaifulah Yophi Ardiyanto; Tengku Arif Hidayat (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
The legal arrangement of cannabis in Indonesia is based on Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia which guarantees the right to health services, elaborated through Law Number 35 of 2009 concerning Narcotics and Law Number 17 of 2023 concerning Health. Cannabis is classified as a Group I narcotic prohibited for health services under Article 8 paragraph (1) of Law Number 35 of 2009, while Article 139 of Law Number 17 of 2023 requires that the use of medicines containing narcotics may only be carried out based on a prescription from medical personnel. At the same time, Canada through the Cannabis Act (S.C. 2018, c. 16) and Uruguay through Ley No. 19.172 (2013) apply fundamentally different legal arrangements for cannabis. This research uses normative legal research methods with a comparative law approach, applying the criminal policy framework of Marc Ancel and the law enforcement theory of Joseph Goldstein. The results show: (1) cannabis arrangement in Indonesia is prohibitive through Article 8 paragraph (1) of Law Number 35 of 2009, while Article 6 paragraph (3) opens a mechanism for reclassification through Ministerial Regulation; (2) Canada through the Cannabis Act applies a regulated market model with a CAD 11.4 billion legal industry and a 70% reduction in arrests, while Uruguay through Ley No. 19.172 applies a state monopoly with an 85% reduction in arrests without an increase in problematic use; (3) fundamental differences in legal systems, political systems, socio-cultural backgrounds, religion, and narcotics policy philosophy mean that the Canadian and Uruguayan models are not relevant to be directly applied in the Indonesian criminal law system.